Transcriptomic Profile in CD4 + T Lymphocytes of Patients with Latent and Active Tuberculosis - Tomas Raul Wiche Salinas (2019)
Tuberculosis is an infectious disease cause of a major public health problem worldwide. Every year there are 8.7 million new cases and 1.4 million deads. The present study evaluated and compared the gen expression of CD4+ T cells of latent and active Tuberculosis-infected individuals in the city of Arequipa. CD4+ T cells were isolated by negative selection using magnetic beads from 10 patients with latent and 20 with active tuberculosis. Gen expression of pro-inflammatory cytokines IFN-gamma, IL-17, IL-8 and IL-6, and anti-inflammatory cytokine IL-4 and transcription factor FOXP3 were evaluated by RT-PCR. The present study found a higher expression of IFN-gamma, IL-6, IL-8, and IL-17 in active tuberculosis and a higher expression of IL-4 and FOXP3 in active tuberculosis. Understanding the immunological mechanism associated with latent and active tuberculosis will let us understand its pathogenesis.